Supply Chain Finance and the Sustainable Growth of Chinese Firms: The Moderating Effect of Digital Finance - Liu, Tinghua; Liu, Weiya; Elahi, Ehsan; Liu, Xiao (Frontiers in Environmental Science, 2022)
Sustainable development is crucial to the survival and healthy development of enterprises, which is closely related to their financing situation. Supply chain finance is an effective way to improve and enhance the financing situation by easing financing constraints and reducing financing costs. As an important source of supply chain short-term financing, trade credit plays an important role in enterprise production and circulation. Taking Chinese listed companies from 2011 to 2020 as samples, this paper studied the impact of trade credit on sustainable growth and its internal mechanism. Furthermore, we analyzed the moderating effect of digital finance development on the influence of trade credit on sustainable growth. It is found that receiving trade credit benefited firms’ sustainable growth. Furthermore, study found that receiving trade credit has a greater positive impact on the sustainable growth of enterprises in regions with higher levels of financial development, high-tech industries, state-owned enterprises and small enterprises. Whereas, the provision of trade credit had an obvious inhibiting effect on the sustainable growth of enterprises in the regions with low level of financial development, non-high-tech industries, private enterprises and small enterprises. The results of the influencing mechanism showed that receiving trade credit promoted firm's sustainable growth by “agency cost reducing effect”, while providing trade credit inhibited firm's sustainable growth by “forcing effect”. In addition, the development of digital finance weakens the positive impact of trade credit financing on enterprises’ sustainable growth but strengthens the negative impact of providing trade credit on sustainable growth.